(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article presents an analysis of the democratic nature of the political system of Kyrgyzstan, which is determined by the fundamental document - the Constitution, which fixes human rights, pluralism, and principles of representation. In the process of analysis, it was revealed that the principle of constitutional government, which went through a complex path of formation and evolution, became the material embodiment of the idea of limiting the actions of government within the framework of popular consent. The concepts of parliamentarism and constitutionalism adopted in many states allow us to recognize that these are ideas laid down for the future and are resolved through the prism of democratic principles of representative government. It is concluded that almost all constitutions contain a declaration about the main bodies of the state and branches of government, the power prerogatives assigned to them, as well as how they are interconnected, and how they restrain and limit each other, which is important for building Kyrgyz democratic institutions